Software reliability techniques for real-world applications - Youree, Roger K. (Wiley series in quality and reliability engineering., 2023)
"Software controls a lot of aspects in our everyday lives, such as our home appliances, phones, cars, and many other computerized entertainment options. Because we are so dependent on it, it is important that software is reliable at all times, and this is where software reliability comes into play. Software reliability is the probability of a failure-free operation of a computer program / device and helps to find defects where humans are unable to do so. The importance of software reliability, along with its complexity and external constraints, mean that a software reliability program should be planned and implemented early in development and monitored and adjusted as needed"--